A hybrid 3D SEM reconstruction method optimized for complex geologic material surfaces. (August 2017) - Yan, Shang; Adegbule, Aderonke; Kibbey, Tohren C.G.
Graphical abstract: Highlights: A hybrid reconstruction method is developed combining stereo and shape-from-shading. The method is optimized for extracting detail from rough natural surfaces. Equations are derived based on secondary electron detector response. A sphere image is used to calculate detector position and response. The method is able to capture angular features, sharp edges, and surface striations. Abstract: Reconstruction methods are widely used to extract three-dimensional information from scanning electron microscope (SEM) images. This paper presents a new hybrid reconstruction method that combines stereoscopic reconstruction with shape-from-shading calculations to generate highly-detailed elevation maps from SEM image pairs. The method makes use of an imaged glass sphere to determine the quantitative relationship between observed intensity and angles between the beam and surface normal, and the detector and surface normal. Two specific equations are derived to make use of image intensity information in creating the final elevation map. The equations are used together, one making use of intensities in the two images, the other making use of intensities within a single image. The method is specifically designed for SEM images captured with a single secondary electron detector, and is optimized to capture maximum detail from complex natural surfaces. The method is illustrated with a complex structured abrasive material, and a rough natural sand grain. Results show that the method is capable of capturing details such as angular surface features, varying surface roughness, and surface striations.